Layered manganese oxide molded body and method for producing same
Patent Information
- Application Number
- JP2021562706
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-06
- Filing Date
- 2020-12-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-12-03
AI Technical Summary
【0018】 本発明は、実際の原子力発電汚染水処理設備での使用形態を鑑みて、ストロンチウム吸着性能と機械的強度、保形性とを両立し、吸着に不活性な結合剤を含まない層状マンガン酸化物成形体を、簡便かつコストに優れる製造方法で提供可能である。
Smart Images

Figure 0007638899000002 
Figure 0007638899000003 
Figure 0007638899000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a layered manganese oxide molded body and a method for producing the same. [Background technology]
[0002] The operation of adsorbing and separating harmful or useful ions from an aqueous solution using a solid-phase adsorbent is important as a separation technique because it does not involve the high-cost concentration of the aqueous solution. In particular, the adsorption of strontium ions is particularly important because strontium is produced in large amounts in fission products in uranium fission nuclear power generation and the wastewater standard value for strontium concentration is low. Manganese oxide has been widely known as a material capable of selectively adsorbing and separating strontium.
[0003] Patent Document 1 discloses a layered manganese oxide having sodium ions between layers, which is synthesized by a solid-state reaction method in which manganese raw materials and sodium raw materials are mixed and fired as an adsorbent for strontium ions in seawater.
[0004] Similarly, Patent Document 2 discloses a layered manganese oxide having potassium ions between layers, which is synthesized by a solid-state reaction method in which manganese raw materials and potassium raw materials are mixed and fired, as an adsorbent for strontium ions in seawater.
[0005] Furthermore, birnessite-type layered manganese oxide is disclosed as an adsorbent for radioactive nuclides including strontium in Non-Patent Document 1. This substance is obtained by reacting a sol of manganese hydroxide with magnesium permanganate and aging it under highly alkaline conditions (pH 13.7) for 7 days.
[0006] However, all of these documents only describe the adsorption performance of the powder, and there is no mention of the performance of the molded body. When considering the actual use of the adsorbent in the contaminated water treatment facility of a nuclear power plant, it is not necessary to use the powder form, which has high pressure loss and complicated disposal, and is rather inconvenient. For this purpose, it is assumed that the powder will be used as a molded body that can be filled into an adsorption tower, has low pressure loss, and is easy to dispose of. It goes without saying that such molded bodies are required to have not only strontium adsorption performance, but also secondary functions such as mechanical strength and shape retention in a dry state or when seawater is passing through it. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] WO2017 / 086056A1 [Patent Document 2] WO2018 / 110615A1 [Non-patent literature]
[0008] [Non-Patent Document 1] DYER Alan et al., Sorption characteristics of radionuclides on synthetic birnessite-type layered manganese oxides, J. Mater. Chem., 2010, vol. 10, pp. 1867-1874 Summary of the Invention [Problem to be solved by the invention]
[0009] It is difficult to produce a compact by agglomeration of layered manganese oxide synthesized by the conventional solid-state reaction method. Therefore, the addition of an inorganic binder is essential to achieve a strength suitable for use as a compact. However, since an inorganic binder does not contribute to strontium adsorption, its use leads to a decrease in adsorption performance. Also, the adsorption utilization rate of layered manganese oxide decreases when the adsorption surface is covered and blocked with an inorganic binder. In addition, when using extrusion molding or the like for a kneaded product of an inorganic binder and layered manganese oxide, an additional process of thickening with an organic compound may be required. If such a compact treated with an organic compound is used for the treatment of contaminated water from a nuclear power plant, the mechanical strength of the compact will inevitably decrease due to alteration caused by radiation. In addition, there is a concern that the layered manganese oxide will be reduced and decomposed when the organic compound is oxidized and burned by heat treatment.
[0010] Furthermore, compacts prepared from layered manganese oxide powder synthesized by a solid-state reaction method and an inorganic binder often have a low bulk density. When filling an adsorption tower of a certain volume with layered manganese oxide compacts, a higher bulk density allows a larger weight to be filled, which results in a higher strontium adsorption capacity. In this respect, too, it is advantageous that the compact does not contain any components other than the adsorbent, such as a binder, and has a high bulk density.
[0011] Furthermore, layered manganese oxide molded bodies synthesized by the solid-state reaction method have poor shape retention when passing water through them. If the shape retention is poor, they may become finely powdered and clog the adsorption tower flow path, or become muddy and difficult to handle when removed from the adsorption tower. For this reason, it is expected that using layered manganese oxide molded bodies synthesized by the solid-state reaction method to treat contaminated water from nuclear power plants would pose a major problem when disposing of the radioactive molded bodies.
[0012] Therefore, there was an urgent need to develop a molded product that had the desired strontium adsorption performance, mechanical strength, and shape retention, and that contained as much layered manganese oxide content as possible and was free of inorganic binders and organic substances, and a method for producing the same.
[0013] The present invention solves these problems, and provides a layered manganese oxide molded body that simultaneously achieves sufficient strontium adsorption performance, mechanical strength, and shape retention without any problems.
[0014] Furthermore, when the layered manganese oxides shown in patent and non-patent documents are used as molded bodies, complicated production steps are required, such as obtaining layered manganese oxide powder by a solid-phase synthesis method in which raw materials are mixed and fired, or by a wet synthesis method in which a permanganate and a manganese salt are reacted in an aqueous solution, adding and kneading an inorganic binder and an organic thickener, forming the resulting product into noodles using an extrusion molding machine, drying, and then crushing.
[0015] The present invention solves this problem, and the layered manganese oxide molded body of the present invention can be produced through simple steps of a wet reaction, followed by filtration, drying and crushing. [Means for solving the problem]
[0016] The present inventors have conducted extensive research into a layered manganese oxide molded body having excellent strength, shape retention, and strontium adsorption performance, and have found that the strength, shape retention, and adsorption performance are all satisfactory at a high level, leading to the completion of the present invention.
[0017] That is, the layered manganese oxide molded product according to one embodiment of the present invention is composed of a layered manganese oxide containing at least an alkali metal and manganese, has a crushing strength of 1000 mN or more and 5000 mN or less as measured by a microcompression tester, contains no inorganic binders or organic components, has a particle size of 0.2 mm or more and 1.7 mm or less for 90% or more of the total particles, and has a bulk density of 0.9 g / cm 3 That's all. Effect of the Invention
[0018] In view of the actual use in nuclear power plant contaminated water treatment facilities, the present invention can provide a layered manganese oxide molded body that combines strontium adsorption performance with mechanical strength and shape retention and does not contain a binder that is inactive to adsorption, using a simple and cost-effective production method. [Brief description of the drawings]
[0019] [Figure 1] 1 is a powder X-ray diffraction pattern of the layered manganese oxide of Example 1. [Diagram 2] 1 is a scanning electron microscope image of a layered manganese oxide molded body of Example 1. [Diagram 3] 1 shows powder X-ray diffraction patterns of the layered manganese oxides of Example 2 (samples A and B). [Figure 4] 1 is a scanning electron microscope image of a layered manganese oxide molded body of Example 2. [Diagram 5] 1 is a powder X-ray diffraction pattern of the layered manganese oxide of Example 3. [Figure 6] 1 is a scanning electron microscope image of a layered manganese oxide molded body of Example 3. [Figure 7] 1 is a powder X-ray diffraction pattern of the layered manganese oxide of Example 4. [Figure 8] 1 is a scanning electron microscope image of a layered manganese oxide molded body of Example 4. [Figure 9] 1 is a powder X-ray diffraction pattern of the layered manganese oxide of Comparative Example 1. [Figure 10] 1 is a scanning electron microscope image of a layered manganese oxide molded body of Comparative Example 1. [Figure 11] 1 is a powder X-ray diffraction pattern of a manganese oxide molded body of Comparative Example 2. [Figure 12] 1 is a powder X-ray diffraction pattern of the layered manganese oxide of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below.
[0021] The layered manganese oxide molded article of the present invention is composed of a layered manganese oxide containing at least an alkali metal and manganese. x MnO 2 A layered A-Mn oxide, where A is at least one alkali metal selected from sodium and potassium, is preferred in that there is no difference in crystal lattice size between dry and wet states and collapse of the compact when water is passed through it can be suppressed. At least one of sodium and potassium can be used as the alkali metal, and a mixture of both alkali metals is also possible. The alkali metal is preferably potassium, since it can suppress the lattice volume change of the layered manganese oxide compact of the present invention when dry and wet, and can maintain the shape retention when water is passed through it. A is an alkali metal, and x represents the A / Mn molar ratio, that is, the range of x can be expressed as 0.2≦x≦0.6, and among them, when 0.3≦x≦0.5, the strontium adsorption performance of the layered manganese oxide compact of the present invention is high, and it is more preferred. Furthermore, it was found that a layered manganese oxide compact containing both alkali metals sodium and potassium and having 0.4≦x≦0.6 has higher strontium adsorption performance. The oxygen composition can be regarded as an integer value of 2, although there is some variation due to vacancy generation, etc. Furthermore, water may be present between the layers or between the particles of the layered manganese oxide constituting the manganese oxide molded article of the present invention.
[0022] In order to suppress the volume change of the layered manganese oxide molded product of the present invention from a dry state to a wet state, the interlayer distance of the constituent layered manganese oxide is preferably 7.0 angstroms or more and 7.3 angstroms or less. If it exceeds this range, the volume change from a dry state to a wet state may cause distortion inside the molded product, and the layered manganese oxide molded product of the present invention may collapse. The interlayer distance of the layered manganese oxide molded product of the present invention is obtained by converting the 001 peak position (angle), which is the lowest angle diffraction peak in the powder X-ray diffraction pattern and belongs to a hexagonal crystal, into the interplanar spacing (angstroms).
[0023] In addition, the lower the crystallinity of the layered manganese oxide shaped body of the present invention, the more advantageous it is for increasing the strontium adsorption capacity. For this reason, in powder X-ray diffraction measurement, it is preferable for the full width at half maximum (FWHM) of the 001 peak when assigned to a hexagonal crystal to be large. Specifically, the FWHM is preferably 0.4° to 3.5°, more preferably 0.4° to 3.0°, and even more preferably 0.7° to 2.2°. Furthermore, in the case where the layered manganese oxide shaped body contains both alkali metals, sodium and potassium, and where 0.4≦x≦0.6, the layered manganese oxide shaped body having a 001 peak FWHM of 2.5° to 3.5° when assigned to a hexagonal crystal in a powder X-ray diffraction experiment has been found to have higher strontium adsorption performance.
[0024] The layered manganese oxide molded body of the present invention is characterized by a high crushing strength of 1000 mN or more and 5000 mN or less, as measured by a microcompression tester. If the crushing strength is less than 1000 mN, the mechanical strength is insufficient, and if it exceeds 5000 mN, the porosity is lost, resulting in a decrease in strontium adsorption performance. From the standpoint of shape retention and strontium adsorption performance, the crushing strength is preferably 2000 mN or more and 4000 mN or less.
[0025] The layered manganese oxide molded body of the present invention preferably has an agitation abrasion degree, which is an index for evaluating the shape retention of the molded body when water is passed through it, of 15% by weight or less. The agitation abrasion degree can be measured in accordance with JIS-K-1464 (abrasion test for industrial desiccants).
[0026] The layered manganese oxide shaped body of the present invention is characterized by not containing inorganic binders and organic components. Here, not containing inorganic binders and organic components means that they are below the detection limit in each measurement means. By being substantially free of inorganic binders and organic components that do not function in adsorption, it is possible to improve the adsorption performance and maintain the strength and shape retention of the shaped body. Common inorganic binders include colloidal particles of silicon, aluminum, titanium, and zirconium components, as well as layered or fibrous silicates, specifically bentonite and sepiolite, and the layered manganese oxide shaped body of the present invention does not contain these. Furthermore, the shaped body does not contain organic components, and it is preferable that the carbon concentration in the shaped body is 3000 ppm or less, that is, below the detection limit in each measurement means. Common carbon amount measurement means include CO or CO generated by high-temperature combustion of a sample. 2 It can be found by calculating backwards from the quantity.
[0027] The layered manganese oxide molded body of the present invention does not contain any inorganic binder or organic thickener, so the entire molded body functions in adsorption and increases the bulk density, making it possible to pack a larger weight of adsorbent into an adsorption tower of a given volume. Furthermore, despite not using a binder, the electrostatic aggregation of the particles alone can achieve strong mechanical strength and shape retention when water is passed through it.
[0028] In the layered manganese oxide molded body of the present invention, 90% or more of the total particles are particles with a particle size of 0.2 mm or more and 1.7 mm or less. If the particles with a particle size of 0.2 mm or more and 1.7 mm or less make up less than 90% of the total particles, the particle size distribution becomes broad, and the performance of the adsorption tower decreases. If the particles with a particle size of less than 0.2 mm make up more than 10% of the total particles, there is a drawback in that the pressure loss increases when the molded body is packed into an adsorption tower. On the other hand, if the particles with a particle size of more than 1.7 mm make up more than 10% of the total particles, the liquid contact surface area decreases, and the adsorption performance decreases significantly. It is preferable that 95% or more of the total particles have a particle size of 0.2 mm or more and 1.7 mm or less. It is also preferable that 90% or more of the total particles have a particle size of 0.3 mm or more and 1.0 mm or less. These particle sizes are based on the assumption that the particles will be packed into an adsorption tower of an actual nuclear power plant contaminated water treatment facility.
[0029] The layered manganese oxide molded body of the present invention has a bulk density of 0.9 g / cm 3 It is characterized in that it is 1.0 g / cm or more. 3 Bulk density is preferably 0.9 g / cm or more. 3 If it is less than this, the weight of the molded article that can be packed into a certain volume becomes small, resulting in a reduced adsorption capacity.
[0030] Next, the production of the layered manganese oxide molded body of the present invention will be described. The layered manganese oxide molded body of the present invention can be obtained through step 1 of obtaining a mixed aqueous solution by mixing an aqueous metal salt solution containing at least manganese, an aqueous alkali metal solution, and an oxidizing agent at an alkali metal / manganese molar ratio of 2 to 10, an oxidation-reduction potential of the reaction solution being -0.2 V to 0.6 V versus saturated calomel electrode, and a temperature of 0°C to 100°C, and precipitating layered manganese oxide in the mixed aqueous solution, and step 2 of filtering the precipitated layered manganese oxide and then thermally curing the precipitated material at 40°C to 200°C.
[0031] The manganese-containing metal salt aqueous solution used in step 1 can be prepared by dissolving a manganese-containing metal salt in water. Examples of manganese-containing metal salts include water-soluble manganese sulfate (II), manganese chloride (II), manganese nitrate (II), and manganese acetate (II), and may be anhydrous or hydrated. Of these, manganese sulfate (II) is most suitable in consideration of waste liquid treatment, corrosiveness, and raw material costs. In addition, it is also possible to use a mixture of manganese and other metal ions as long as it does not inhibit the production of layered manganese oxide. It is essential that the alkaline earth metal concentration in the metal salt aqueous solution is low, and the total alkaline earth metal concentration must be less than 1500 ppm. When a raw material solution with an alkaline earth metal concentration of 1500 ppm or more is used, a by-product phase is generated and manganese oxide with a developed layered structure is not obtained, resulting in a decrease in strontium adsorption performance. The total alkaline earth metal concentration is preferably less than 1000 ppm, more preferably 500 ppm, and even more preferably less than 100 ppm. The total concentration (metal concentration) of all metals such as manganese in the aqueous metal salt solution is not limited, but since the metal concentration affects productivity, it is preferably 1.0 mol / L or more, and more preferably 2.0 mol / L or more.
[0032] The aqueous alkali metal solution used in step 1 can be prepared by dissolving an alkali metal compound in water. As the alkali metal compound, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an alkali metal carbonate such as sodium carbonate or potassium carbonate is preferable in terms of water solubility, cost, and pH adjustment. From the viewpoint of productivity, the alkali metal concentration of the aqueous alkali metal solution can be, for example, 1 mol / L or more. The molar ratio of alkali metal / manganese is 2 or more and 10 or less. If it is less than 2, the concentration of manganese tetroxide (Mn 3 O 4 ) is produced as a by-product, and even if it exceeds 10, 3 O 4 From the viewpoint of strontium adsorption performance, it is preferable that the ratio is 3 or more and 8 or less.
[0033] Examples of the oxidizing agent used in step 1 include hydrogen peroxide, oxygen, air, and peroxodisulfate. Examples of peroxodisulfate include sodium peroxodisulfate, potassium peroxodisulfate, and ammonium peroxodisulfate. Among these, hydrogen peroxide, oxygen, or air is preferred in terms of ease of raw material procurement and cost. Furthermore, oxygen or air is more preferred from an economical standpoint, and air is more preferred. Gas such as air or oxygen is added by bubbling it into the mixed aqueous solution using a bubbler or the like.
[0034] In step 1, the redox potential of the reaction solution is adjusted to -0.2 V to 0.6 V based on the saturated calomel electrode to obtain a mixed aqueous solution, from which the layered manganese oxide of the present invention precipitates. If the redox potential is outside this range, Mn 3 O 4 and permanganate are produced. Mn 3 O 4 is inactive in strontium adsorption, and its formation leads to a decrease in strontium adsorption performance. Similarly, if the redox potential is outside this range, the strength of the layered manganese oxide shaped article of the present invention decreases. A more preferable range of the redox potential is from -0.1 V to 0.5 V based on the saturated calomel electrode. The redox potential of the reaction solution is a value based on a general standard hydrogen electrode, and can be determined by a commercially available redox potentiometer. The redox potential can be controlled by the amount of oxidizing agent supplied and the reaction temperature.
[0035] In step 1, the temperature at which the manganese-containing metal salt aqueous solution, the alkali metal aqueous solution, and the oxidizing agent are mixed is 0° C. or higher and 100° C. or lower. If the mixing temperature is below 0° C., the oxidation reaction will not proceed and the reaction liquid may solidify, while if it exceeds 100° C., particle growth will proceed and the intended dense aggregates will not be obtained. A temperature of 40° C. or higher and 80° C. or lower is preferred, as the oxidation reaction will proceed more easily and layered manganese oxide will be more likely to precipitate.
[0036] In step 1, when the manganese-containing metal salt aqueous solution, the alkali metal aqueous solution, and the oxidizing agent are mixed, either a batch type or a continuous type reaction may be used. The pH at the end of mixing is preferably 7 to 14, and the pH and the redox potential of the reaction solution can be appropriately adjusted by controlling the input rate of either the manganese-containing metal salt or the alkali metal aqueous solution. In addition, as for the method of adding the metal aqueous solution and the alkali metal aqueous solution, it is preferable to simultaneously drop them at a constant rate while keeping the alkali metal / manganese molar ratio constant, since this results in a compact molded body that is dense and has high strength and adsorption performance. Furthermore, as for the stirring during mixing, the stirring power required when mixing at least the manganese-containing metal salt aqueous solution, the alkali metal aqueous solution, and the oxidizing agent is 0.5 kW / m 3 The required mixing power is 0.5kW / m 3 If the mixing is insufficient, such as less than 1 kW / m, a by-product phase is generated and the desired dense aggregates cannot be obtained. 3 More than 5kW / m is preferable. 3 Above is more preferable.
[0037] The solids concentration in the slurry obtained by mixing the raw material liquids in step 1 must be 1 wt% or more and 5 wt% or less. A high concentration is desirable to ensure productivity, but if the concentration exceeds 5 wt%, dense aggregates tend not to be obtained. In this case, a concentration of 3 wt% or more and 4 wt% or less is preferable to achieve both production efficiency and denseness.
[0038] In step 2, the method for filtering the layered manganese oxide precipitated in step 1 is not particularly limited as long as it allows solid-liquid separation. Industrially, a belt filter, a filter press, a pressure filter, an ultrafilter, or the like can be used. The layered manganese oxide may be washed during filtration.
[0039] In step 2, the layered manganese oxide is thermally cured to produce the layered manganese oxide molding of the present invention, and the temperature is preferably 40°C to 200°C, and more preferably 40°C to 160°C, from the viewpoint of the shape retention of the layered manganese oxide molding of the present invention. The thermal curing treatment may also serve as a treatment for drying the filter cake of the layered manganese oxide obtained by filtration. By this thermal curing treatment, the buserite-type layered manganese oxide with an interlayer distance of 9 to 10 angstroms obtained in step 1 is changed to a birnessite-type layered manganese oxide with an interlayer distance of 7.0 to 7.3 angstroms, and the volume of the filter cake shrinks (densifies) and heat hardens. The thermal curing treatment is performed with the filter cake in its original shape or after it has been appropriately crushed or shaped. The time of the thermal curing treatment is appropriately determined according to the progress of the curing. As described above, by using mild drying conditions, a granular compact that is an aggregate with high hardness and high density can be obtained, and this can be achieved by appropriately controlling the heat curing conditions (dried shape of the filter cake, temperature, and time). Rotary drying and flash drying are unsuitable because they tend to form particles with a particle size of less than 0.2 mm.
[0040] The layered manganese oxide molded product of the present invention is formed by thermally curing the filter cake, followed by crushing and classification as necessary, so that 90% or more of the total particles have a particle size of 0.2 mm or more and 1.7 mm or less. There are no particular limitations on the crushing method, and crushing can be carried out using a general crusher, for example, a crusher-type crusher such as a cone crusher or a roll crusher, or a mill-type crusher such as a cutter mill, a stamp mill, a ring mill, a roller mill, a jet mill, a hammer mill, a rotary mill (ball mill), or a vibration mill. As for the classification method, either a dry classification method or a wet classification method can be used, and classification can be carried out appropriately using a hydraulic classifier, a sedimentation classifier, a mechanical classifier, an air classifier, a gravity classifier, a cyclone classifier, a sieve classifier, or the like.
[0041] The layered manganese oxide shaped body of the present invention can be used, for example, as an adsorbent for strontium or for adsorbing other heavy metals.
[0042] As a strontium adsorbent, it is useful for selectively adsorbing strontium from a treatment solution containing a large amount of various coexisting ions.
[0043] 〔summary〕 As described above, the present invention comprises the following configurations.
[0044] [1] It is composed of layered manganese oxide containing at least an alkali metal and manganese, has a crushing strength of 1000 mN to 5000 mN when measured with a microcompression tester, does not contain inorganic binders or organic components, has a particle size of 0.2 mm to 1.7 mm or more, and has a bulk density of 0.9 g / cm. 3 The above is the layered manganese oxide molded body.
[0045] [2] Composition formula A x MnO 2 A is at least one alkali metal selected from sodium and potassium, and 0.2≦x≦0.6.
[0046] [3] The layered manganese oxide molded product according to [1] or [2] above, wherein the interlayer distance of the layered manganese oxide is from 7.0 angstroms to 7.3 angstroms.
[0047] [4] The layered manganese oxide molded body according to any one of the above [1] to [3], wherein the FWHM of the 001 peak when assigned to a hexagonal crystal in a powder X-ray diffraction experiment is 0.4° or more and 3.5° or less.
[0048] [5] Composition formula A x MnO 2 A layered manganese oxide molded body according to any one of items [1] to [4] above, wherein A is an alkali metal containing at least sodium and potassium, 0.4≦x≦0.6, and the FWHM of the 001 peak when assigned to a hexagonal crystal in a powder X-ray diffraction experiment is 2.5° or more and 3.5° or less.
[0049] [6] The layered manganese oxide molded body according to any one of the above [1] to [5], wherein the alkali metal is potassium.
[0050] [7] The layered manganese oxide molded product according to any one of the above [1] to [6], which has a stirring wear rate of 15% by weight or less.
[0051] [8] The layered manganese oxide molded product according to any one of the above [1] to [7], wherein the inorganic binder is at least one inorganic binder selected from the group consisting of silicon, aluminum, titanium and zirconium components.
[0052] [9] The layered manganese oxide molded product according to any one of the above [1] to [8], which has a carbon concentration of 3000 ppm or less.
[0053]
[10] A metal salt aqueous solution containing at least manganese and with an alkaline earth metal concentration of less than 1500 ppm, an alkali metal aqueous solution, and an oxidizing agent are mixed in a solution having an alkali metal / manganese molar ratio of 2 to 10, an oxidation-reduction potential of -0.2 V to 0.6 V based on the saturated calomel electrode, a temperature of 0°C to 100°C, and a stirring power requirement of 0.5 kW / m 3 The method for producing a layered manganese oxide molded product according to any one of the above [1] to [9], comprising: obtaining a mixed aqueous solution by mixing the above; precipitating a slurry in the mixed aqueous solution to a solids concentration of 1 wt% or more and 5 wt% or less; filtering the resultant precipitate; and thermally curing the precipitate at a temperature of 40°C or more and 200°C or less.
[0054]
[11] The method for producing a layered manganese oxide molded body according to
[10] above, wherein the alkali metal is potassium.
[0055]
[12] The method for producing a layered manganese oxide molded product according to
[10] or
[11] above, wherein the oxidizing agent is at least one selected from the group consisting of hydrogen peroxide, oxygen, air, and peroxodisulfates.
[0056]
[13] The method for producing a layered manganese oxide molded product according to any one of the above
[10] to
[12] , wherein the precipitated substance precipitated in the mixed aqueous solution is buserite having an interlayer distance of 9 angstroms or more and 10 angstroms or less, and the precipitated substance becomes birnessite having an interlayer distance of 7.0 angstroms or more and 7.3 angstroms or less during a thermal curing process.
[0057]
[14] A strontium adsorbent comprising the layered manganese oxide molded article according to any one of the above [1] to [9]. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.
[0059] <Measurement of elemental composition> The elemental composition of the obtained sample was analyzed by inductively coupled plasma emission spectrometry (ICP method). That is, the sample powder was dissolved in pressurized acid with hydrogen peroxide water and hydrofluoric acid to prepare a measurement solution. The elemental composition of the obtained sample was analyzed by measuring the measurement solution using an inductively coupled plasma emission spectrometry device (product name: OPTIMA3000DV, manufactured by PERKIN ELMER).
[0060] <Measurement of carbon concentration> The carbon concentration of the samples was analyzed using a fully automatic elemental analyzer (PE2400 Series 2 CHNS / O Analyzer, manufactured by PerkinElmer).
[0061] Measurement conditions: Combustion temperature 950℃, reduction temperature 640℃ <Powder X-ray diffraction measurement> The obtained samples were subjected to powder X-ray diffraction measurement using a powder X-ray diffractometer (product name: Ultima4, manufactured by Rigaku). The radiation source was CuKα radiation (λ = 1.5405 Å), the measurement mode was step scan, the scan conditions were 0.04° per second, the measurement time was 0.25 seconds, and the measurement range was 5° to 90° as 2θ.
[0062] <Crushing strength measurement> The crushing strength of the samples was measured using a micro-compression tester (product name: MCT-510, manufactured by Shimadzu Corporation). The crushing strength was measured by applying a load to the sample using a diamond platen. A randomly selected compact granule was placed on the sample stage, and the diamond platen was automatically lowered. The test force at which the particles collapsed was taken as the crushing strength. The crushing strength was taken as the test force at which the displacement of the diamond platen under load was the largest. The displacement that was considered to be the minute movement of the particles before collapse, as observed through a microscope, was excluded.) This measurement was repeated 25 times, and the average value was taken as the crushing strength of the compact.
[0063] <Measurement of agitation wear> The abrasion degree was measured in accordance with JIS-K-1464 (abrasion test of industrial desiccants) and US Patent No. 5925284. That is, 7.5 g of water and 2.5 g of the molded body in dry weight were placed in a 30 mL wide-mouth polyethylene bottle and left to stand at 25 ° C for 24 hours. The polyethylene bottle was shaken and agitated for 5 minutes using a paint shaker (manufactured by Toyo Seiki Seisakusho), and the fallen material that had fallen off the molded body due to abrasion was separated and collected by sieving it through a 100 mesh (opening 150 μm), and the weight of the fallen material after drying at 200 ° C for 12 hours was calculated using the following formula.
[0064] Abrasion rate (wt%) = (weight of fallen material / dry weight of compact before agitation) x 100 <Measurement of bulk density> The bulk density of the sample was measured by the following method. 5 g of the dry weight of the compacts classified into particle sizes of 0.3 to 0.6 mm was weighed out. This predetermined weight of the compacts was allowed to fall naturally into a graduated cylinder, the volume was read from the graduated cylinder scale, and the bulk density was calculated by the following formula.
[0065] Bulk density = W / V (g / cm 3 ) W: Dry weight of layered manganese oxide compact (g) V: Measuring cylinder reading (cm 3 ) <Strontium adsorption test> Contaminated seawater was simulated by weighing out the specified amounts of sodium chloride, strontium chloride hexahydrate, calcium chloride, magnesium chloride hexahydrate, and cesium chloride reagents and diluting them with pure water to obtain a concentration of NaCl: 0.3%, Ca 2+ : 5 ppm, Mg 2+ : 2 ppm, Sr 2+ : 5 ppm, Cs + : Liquid A to be treated (hereinafter referred to as "simulated seawater A") with pH 7 and 1 ppm, NaCl: 0.3%, Ca 2+ : 70ppm, Mg 2+ : 40 ppm, Sr 2+ : 5 ppm, Cs + The treated liquid B (hereinafter referred to as "simulated seawater B") was prepared with a pH of 7 and a concentration of 1 ppm. The pH of the treated liquid A was adjusted with a 1N-NaOH aqueous solution to obtain a concentration of 0.3% NaCl and 0.3% Ca. 2+ : 5 ppm, Mg 2+ : 0 ppm, Sr 2+ : 5 ppm, Cs + A treatment liquid C (hereinafter referred to as "simulated seawater C") having a pH of 12 and a concentration of 1 ppm was prepared.
[0066] The layered manganese oxide molded body was immersed in water for 30 minutes to remove the air, and then 5 mL of the mixture was loaded into a column with an inner diameter of 8 mm. Pure water was passed through the column at a rate of 100 mL / hr for 1 hour, and then, while maintaining the column temperature at 30°C, simulated seawaters A to C were passed through the column at a rate of 100 mL / hr. The treated simulated seawaters obtained by passing the liquids through the column (hereinafter referred to as "treated liquids A to C") were sampled in 100 mL portions every 24 hours thereafter.
[0067] The strontium concentration in the treatment solution was measured by inductively coupled plasma emission spectrometry (ICP method). A general inductively coupled plasma emission spectrometry device (product name: OPTIMA3000DV, manufactured by PERKIN ELMER) was used for the measurement, and the strontium concentration was obtained by measuring the treatment solution.
[0068] The strontium concentration in the simulated seawater before the adsorption test was C 0 (mg / L), the strontium concentration of the treated liquid is C (mg / L), and C / C 0was plotted against the total simulated seawater flow rate per unit volume of adsorbent (hereinafter referred to as "BV") from the start of the simulated seawater flow to the sampling time, and C / C 0 = 0.1 (hereinafter referred to as "breakthrough BV").
[0069] <Method for measuring the weight fraction of particles with a particle size of 0.2 mm or more and 1.7 mm or less> The sample was passed through metal sieves with 1.7 mm (10 mesh) and 0.21 mm (70 mesh) openings. The particle weight fraction corresponding to particle sizes between 0.2 mm and 1.7 mm was calculated using the weight A of the particles on the 1.7 mm opening sieve and the weight B of the total particles as follows:
[0070] Weight fraction of particles with particle diameters between 0.2 mm and 1.7 mm (%) = 100 × (BA) / B <How to calculate the power required for mixing> The stirring power required per unit volume was calculated by the following formula.
[0071] P = Np ρ n 3 d 5 Pv=P / V (P: mixing power required [W], Pv: mixing power required per volume [kW / m 3 ], ρ: density [kg / m 3 ], n: rotation speed [rps], d: blade span [m], Np: power number [-], V: volume [L]) For Np: power number, 1.1 was used for the 10 L reactor and paddle impeller, and 1.8 was used for the 1 L reactor and paddle impeller. For other parameters, ρ: density was 1.22 g / cc, d: impeller span was 128 mm for the 10 L reactor and paddle impeller, and 80 mm for the 1 L reactor and paddle impeller, and V: volume was 5 L for the 10 L reactor (Example 3), 0.7 L for the 1 L reactor (Examples 1 and 4 and Comparative Examples 2 and 3), and 0.3 L (Comparative Example 4).
[0072] Example 1 300g of pure water was placed in a 1L reaction vessel, which was heated to 40°C and maintained at that temperature. Separately, manganese sulfate was dissolved in pure water to prepare a metal salt aqueous solution containing 0.82mol / L manganese sulfate. The alkaline earth concentrations of the metal salt aqueous solution were Ca 10ppm, Mg 7ppm, and other alkaline earth metals were below the detection limit. The metal salt aqueous solution was added to the reaction vessel at a feed rate of 10g / min. At the same time, 35% hydrogen peroxide solution was added to the reaction vessel as an oxidizing agent at a feed rate of 5.4g / min. For mixing, a four-blade paddle blade with an outer diameter of 80mm was used to rotate at 600ppm. The stirring power required at this time was 10kW / m 3 In addition, a 5 mol / L aqueous potassium hydroxide solution (alkali metal aqueous solution) was continuously added for 30 minutes so that the redox potential was -0.055 V based on the saturated calomel electrode. The K / Mn molar ratio when the metal salt aqueous solution and 35% hydrogen peroxide solution were supplied was 4.7. By the above operation, a slurry was obtained in which layered manganese oxide was precipitated. The solid concentration of the slurry was 2.8 wt%. The obtained slurry was filtered and washed with pure water, and the washed wet cake was dried at 60°C for 5 hours and thermally cured to obtain layered manganese oxide (K 0.34 MnO 2 ) was obtained as a lump agglomerate. The lump agglomerate was disintegrated by tapping with an alumina mortar and pestle. It was then passed through a mesh with 0.6 mm openings, and the material remaining on the mesh with 0.3 mm openings was collected and classified into 0.3 to 0.6 mm sizes, to obtain a layered manganese oxide compact.
[0073] The obtained layered manganese oxide compact was found to have a layered crystal structure by powder X-ray diffraction measurement, and the diffraction pattern matched that derived from a birnessite-type crystal structure in which potassium ions exist between layers. The interlayer distance was 7.12 angstroms, and the FWHM of the 001 peak when assigned to a hexagonal crystal was 1.500°. Measurement of the elemental composition revealed that the K / Mn molar ratio was 0.34.
[0074] The bulk density of the obtained layered manganese oxide compact was 1.18 g / cm 3The crushing strength was 2339 mN and the abrasion degree of stirring was 2.15% by weight. There was no change in the shape of the layered manganese oxide compact before and after the measurement of the abrasion degree of stirring. The silicon, aluminum, titanium and zirconium concentrations of the compact were below the detection limit as a result of ICP measurement, and the carbon concentration was below the detection limit (3000 ppm or less). A strontium adsorption test was also carried out using simulated seawater A, B and C. The ICP measurement results for the treatment liquids A, B and C showed that C / C 0 The breakthrough BV values up to =0.1 were 4600, 680, and 8340, respectively.
[0075] The measurement results of the layered manganese oxide molded body are shown in Table 1. Furthermore, the powder X-ray diffraction pattern of the layered manganese oxide is shown in Figure 1, and a scanning electron microscope image (SEM image) of the layered manganese oxide is shown in Figure 2.
[0076] [Table 1]
[0077] Example 2 Manganese nitrate hexahydrate (Kanto Chemical special grade, 98%), 52.83 g, was dissolved in a small amount of water, and the manganese nitrate solution was prepared by measuring up to 600 mL using a measuring flask to make the concentration 0.3 mol / L. Potassium hydroxide (KOH) 47.61 g was dissolved in a small amount of water, and hydrogen peroxide (H 2 O 2 , 35%) 51.60 mL was added (H 2 O 2 + KOH aqueous solution). 600 mL was prepared using a measuring flask. The KOH concentration was 1.2 mol / L, H 2 O 2 The concentration was 1.0 mol / L.
[0078] Transfer 600 mL of the manganese nitrate solution to a 2000 mL beaker and add H 2 O 2+ 600mL of KOH aqueous solution was slowly added. After stirring for 10 minutes, the stirring was stopped and the mixture was left to stand for 1 hour. The obtained solid was filtered under reduced pressure using filter paper, washed with 3000mL of water, and thermally cured by drying in a dryer at 60°C for 1 day. The dried product was a shiny aggregated mass, and the yield was 21.12g.
[0079] The bulk agglomerates were placed in an alumina mortar and crushed with a pestle. The crushed pieces were opened and passed through a 0.6 mm mesh, and the pieces remaining on the 0.3 mm mesh were collected and classified into 0.3 to 0.6 mm particles to obtain layered manganese oxide molded bodies.
[0080] After filtration and washing, the powder X-ray diffraction patterns of wet sample A and sample B thermally cured at 60°C for one day are shown in Figure 3. Sample A can be attributed to buserite with an interlayer distance of 9.37 angstroms, and sample B can be attributed to birnessite with an interlayer distance of 7.09 angstroms. The FWHM of the 001 peak was 1.212°. Therefore, it was confirmed that in the process of precipitating in a mixed aqueous solution of manganese nitrate, hydrogen peroxide, and KOH, the precipitated material was buserite with an interlayer distance of 9 angstroms or more and less than 10 angstroms, and that it changed to birnessite with an interlayer distance of 7 angstroms during the thermal curing process.
[0081] The bulk density of the obtained layered manganese oxide compact was 1.19 g / cm 3 The crushing strength was 3426 mN, and the stirring wear degree was 2.87% by weight. There was no change in the shape of the layered manganese oxide compact before and after the stirring wear degree measurement. The silicon, aluminum, titanium, and zirconium concentrations of the compact were below the detection limit as a result of ICP measurement, and the carbon concentration was below the detection limit (3000 ppm or less). The breakthrough BV value in the strontium adsorption test using treatment liquid A was 5105.
[0082] The measurement results of the layered manganese oxide molded body are shown in Table 1. A scanning electron microscope image (SEM image) of the layered manganese oxide is shown in FIG.
[0083] Example 3 2800g of pure water was placed in a 10L reaction vessel, which was heated to 60°C and maintained at that temperature. Separately, manganese sulfate was dissolved in pure water to prepare a metal salt aqueous solution containing 2.0mol / L manganese sulfate. The alkaline earth metal concentrations of the metal salt aqueous solution were Ca22ppm, Mg15ppm, and other alkaline earth metals were below the detection limit. The metal salt aqueous solution was added to the reaction vessel at a feed rate of 35g / min. At the same time, 35% hydrogen peroxide water was added to the reaction vessel as an oxidizing agent at a feed rate of 13g / min. When the metal salt aqueous solution and 35% hydrogen peroxide water were fed, a 5.0mol / L potassium hydroxide aqueous solution was simultaneously dripped so that the K / Mn molar ratio was 4.0. For mixing, a four-blade paddle blade with an outer diameter of 80mm was used to rotate at 600ppm. The stirring power required at that time was 10kW / m 3 The oxidation-reduction potential was -0.062 V versus the saturated calomel electrode. The above procedure yielded a slurry in which layered manganese oxide had precipitated. The solids concentration of the slurry was 2.8 wt%. The resulting slurry was filtered and washed with pure water, and the washed wet cake was then dried at 60°C for 5 hours for thermal curing to obtain layered manganese oxide (K 0.35 MnO 2 ) was obtained as a lump agglomerate. The lump agglomerate was disintegrated by tapping with an alumina mortar and pestle. It was then passed through a mesh with 0.6 mm openings, and the material remaining on the mesh with 0.3 mm openings was collected and classified into 0.3 to 0.6 mm sizes, to obtain a layered manganese oxide compact.
[0084] Powder X-ray diffraction analysis of the obtained layered manganese oxide compact revealed that it contained a small amount of by-product phase, but the main phase was birnessite-type oxide with potassium ions present between the layers. The interlayer distance was 7.09 angstroms, and the FWHM of the 001 peak when assigned to a hexagonal crystal was 1.167°. Measurement of the elemental composition revealed that the K / Mn molar ratio was 0.35.
[0085] The bulk density of the obtained layered manganese oxide compact was 1.39 g / cm 3The crushing strength was 1591 mN and the degree of abrasion by stirring was 4.02% by weight. There was no change in the shape of the layered manganese oxide compact before and after the measurement of the degree of abrasion by stirring. In addition, the silicon, aluminum, titanium and zirconium concentrations of the compact were below the detection limit as a result of ICP measurement, and the carbon concentration was below the detection limit (3000 ppm or less). A strontium adsorption test was also carried out using simulated seawater B. The ICP measurement of treatment liquid B showed that the C / C 0 The breakthrough BV value until the BV reached 0.1 was 2000.
[0086] The measurement results of the layered manganese oxide molded body are shown in Table 1. Furthermore, a powder X-ray diffraction pattern of the layered manganese oxide is shown in Figure 5, and a scanning electron microscope image (SEM image) of the layered manganese oxide is shown in Figure 6.
[0087] Example 4 A 1 L reaction vessel with an outlet at the top was charged with 800 g of pure water, which was heated to and maintained at 60°C. Separately, manganese sulfate was dissolved in pure water to prepare a metal salt aqueous solution containing 0.90 mol / L manganese sulfate. This metal salt aqueous solution was added to the reaction vessel at a feed rate of 10 g / min. At the same time, a 2.3 mol / L potassium hydroxide aqueous solution (alkali metal aqueous solution) was prepared and added to the reaction vessel at a feed rate of 19 g / min. Furthermore, a 10% sodium peroxodisulfate aqueous solution was prepared as an oxidizing agent, and added to the reaction vessel at a feed rate of 18 g / min simultaneously with the metal salt aqueous solution and the alkali metal aqueous solution. The stirring power per volume during mixing was 10 kW / m 3 The above operation was carried out continuously for 4 hours. The slurry from which the layered manganese oxide had precipitated flowed out continuously from the outlet at the top of the vessel. The outflowing slurry was sampled every 40 minutes. The solids concentration of the slurry that flowed out from 200 to 240 minutes after the start of the experiment was 1.8 wt%. The obtained slurry was filtered and washed with pure water, and the washed wet cake was dried at 60°C for 5 hours and thermally hardened to obtain the layered manganese oxide (Na 0.25 K 0.23 MnO 2) was obtained as a lump agglomerate. The lump agglomerate was disintegrated by tapping with an alumina mortar and pestle. It was then passed through a mesh with 0.6 mm openings, and the material remaining on the mesh with 0.3 mm openings was collected and classified into 0.3 to 0.6 mm sizes, to obtain a layered manganese oxide compact.
[0088] The obtained layered manganese oxide compact was found to have a layered crystal structure by powder X-ray diffraction measurement, and the diffraction pattern matched that derived from a birnessite-type crystal structure in which potassium ions exist between layers. The interlayer distance was 7.18 angstroms, and the FWHM of the 001 peak when assigned to a hexagonal crystal was 3.210°. Measurement of the elemental composition revealed that the Na / Mn molar ratio was 0.25 and the K / Mn molar ratio was 0.23.
[0089] The bulk density of the obtained layered manganese oxide compact was 1.33 g / cm 3 The crushing strength was 2069 mN and the abrasion degree of stirring was 0.05% by weight. There was no change in the shape of the layered manganese oxide compact before and after the measurement of the abrasion degree of stirring. Furthermore, the silicon, aluminum, titanium and zirconium concentrations of the compact were below the detection limit as a result of ICP measurement, and the carbon concentration was below the detection limit (3000 ppm or less). A strontium adsorption test was also carried out using simulated seawater A and C. The ICP measurement of treated solutions A and C showed that C / C 0 The breakthrough BV values until =0.1 were 4260 and 9200, respectively.
[0090] The measurement results of the layered manganese oxide molded body are shown in Table 1. Furthermore, a powder X-ray diffraction pattern of the layered manganese oxide is shown in FIG. 7, and a scanning electron microscope image (SEM image) of the layered manganese oxide is shown in FIG.
[0091] Comparative Example 1 Potassium carbonate (special grade reagent, Kishida Chemical) and manganese carbonate (Lianyungang Dongdu Chemical Co., Ltd.) were weighed to a K / Mn molar ratio of 1.0 and mixed in a dry ball mill. The mixed powder was calcined in a muffle furnace under air flow at 300°C for 12 hours and then at 400°C for 6 hours. The calcined product was washed with 5 times the amount of water and filtered, dried overnight at 60°C, and the coarse particles were pulverized in a dry pulverizer (Force Mill, Osaka Chemical) to obtain a potassium-type layered manganese oxide. The obtained potassium-type layered manganese oxide was found to have a layered crystal structure by powder X-ray diffraction measurement, and the diffraction pattern matched that derived from a birnessite-type crystal structure in which potassium ions exist between the layers. The interlayer distance was 7.14 angstroms, the FWHM of the 001 peak when assigned to a hexagonal crystal was 0.577°, and the K / Mn molar ratio calculated from the elemental composition was 0.307.
[0092] Next, the obtained potassium type layered manganese oxide, silica sol and carboxymethyl cellulose (CMC) were mixed in the following weight ratio to obtain a mixture.
[0093] Potassium-type layered manganese oxide: 100 parts by weight Silica in silica sol: 16 parts by weight Water: 36 parts by weight CMC: 5 parts by weight The silica sol used as the inorganic binder had a sol concentration of 48% by weight and an average particle size of 0.02 μm (product name: Snowtex 50-T, manufactured by Nissan Chemical Industries, Ltd.) and was used as the molding aid (product name: Cellogen WS-D, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0094] The resulting mixture was mixed in a Henschel mixer for 20 minutes and then extrusion molded to obtain a cylindrical molded body with a diameter of 1.5 mm. The resulting molded body was fired at 500°C for 3 hours under an air flow of 25 L / min, then crushed and passed through a mesh with 0.6 mm openings. The material remaining on the mesh with 0.3 mm openings was collected and classified into 0.3 to 0.6 mm particles to obtain a layered manganese oxide molded body.
[0095] The bulk density of the obtained layered manganese oxide compact was 0.771 g / cm 3 The crushing strength was 483 mN and the abrasion degree of stirring was 31.0% by weight. There was no change in the shape of the layered manganese oxide compact before and after the measurement of the abrasion degree of stirring. Furthermore, the silicon, aluminum, titanium and zirconium concentrations of the compact were measured by ICP, and the silicon concentration was 6.4 wt%. The carbon concentration was below the detection limit (3000 ppm or less). Furthermore, the breakthrough BV values in the strontium adsorption test using treatment solutions A and B were 2560 and 1210, respectively.
[0096] The measurement results of the layered manganese oxide molded body are shown in Table 1. Furthermore, the powder X-ray diffraction pattern of the layered manganese oxide is shown in Fig. 9, and a scanning electron microscope image (SEM image) of the layered manganese oxide is shown in Fig. 10.
[0097] Comparative Example 2 300g of pure water was placed in a reaction vessel with an internal volume of 1L, and the temperature was raised to 40°C and maintained. An industrial metal salt aqueous solution containing manganese sulfate (manganese sulfate concentration 0.82mol / L) containing alkaline earth metals was used. The alkaline earth metal concentrations in the metal salt aqueous solution were Ca 500ppm, Mg 1400ppm, and other alkaline earth metals were below the detection limit. Synthesis was performed in the same manner as in Example 1, except that the alkaline earth metal concentrations of the manganese sulfate aqueous solution were different.
[0098] The powder X-ray diffraction pattern of the dried sample after filtration and washing is shown in Figure 11. The low-angle 001 peak indicative of a layered structure was hardly observed, indicating that the manganese oxide in question was not a layered manganese oxide.
[0099] The measurement results of the manganese oxide molded body are shown in Table 1.
[0100] Comparative Example 3 The rotation speed of the stirring blade was reduced to 100 rpm, and the required stirring power was reduced to 0.4 kW / m 3 The synthesis was carried out in the same manner as in Example 1, except that the above was used.
[0101] As a result, no dense and hard aggregates were obtained, and it was impossible to use the formed bodies for the adsorption test. The powder X-ray diffraction pattern of the dried sample after filtration and washing is shown in Figure 12. In addition to birnessite-type layered manganese oxide with potassium ions present between the layers, MnOOH and Mn 3 O 4 Since a strong peak was observed, it was confirmed that the sample was a mixed phase of these.
[0102] The measurement results of the layered manganese oxide are shown in Table 1.
[0103] Comparative Example 4 100g of pure water was placed in a reaction vessel with an internal volume of 1L, and the temperature was raised to 40°C and maintained at that temperature. Separately, manganese sulfate was dissolved in pure water to prepare a metal salt aqueous solution containing 2.0mol / L of manganese sulfate. This metal salt aqueous solution was added to the reaction vessel at a feed rate of 5g / min. At the same time, a 10mol / L potassium hydroxide aqueous solution (alkali metal aqueous solution) was added to the reaction vessel at a feed rate of 3.3g / min, and 35% hydrogen peroxide water as an oxidizing agent was added to the reaction vessel at a feed rate of 1.6g / min. The K / Mn molar ratio when the metal salt aqueous solution and 35% hydrogen peroxide water were supplied was 3.0. The stirring power per volume when mixing was 23kW / m 3 The above procedure also yielded a slurry in which layered manganese oxide had precipitated. The solids concentration of the slurry was 6.2 wt%. The resulting slurry was filtered and washed with pure water, and the washed wet cake was then dried at 60°C for 5 hours for thermal curing to obtain layered manganese oxide (K 0.29 MnO 2 ) was obtained as a lump agglomerate. The lump agglomerate was disintegrated by tapping with an alumina mortar and pestle. It was then passed through a mesh with 0.6 mm openings, and the material remaining on the mesh with 0.3 mm openings was collected and classified into 0.3 to 0.6 mm sizes, to obtain a layered manganese oxide compact.
[0104] The obtained layered manganese oxide compact was found to have a layered crystal structure by powder X-ray diffraction measurement, and the diffraction pattern matched that derived from a birnessite-type crystal structure in which potassium ions exist between layers. The interlayer distance was 7.12 angstroms, and the FWHM of the 001 peak when assigned to a hexagonal crystal was 1.440°. Measurement of the elemental composition revealed that the K / Mn molar ratio was 0.34.
[0105] The bulk density of the obtained layered manganese oxide compact was 0.360 g / cm 3 Since the strength of the material was extremely low and the material was fragile, it was difficult to subject the material to an adsorption test.
[0106] The measurement results of the layered manganese oxide molded body are shown in Table 1.
[0107] The entire contents of the specification, claims, drawings and abstract of Japanese Patent Application No. 2019-220928, filed on December 6, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention. [Industrial Applicability]
[0108] The layered manganese oxide molded body of the present invention can be used as an adsorbent for strontium, in particular, it can be used as an adsorbent that selectively adsorbs strontium ions from treated water that contains a large amount of coexisting cations, such as seawater that contains radioactive nuclides derived from uranium fission reactors.
Claims
1. A layered manganese oxide having a composition of A x MnO 2 (A represents one or more alkali metals selected from sodium and potassium, and 0.2≦x≦0.6), a crushing strength of 1000 mN or more and 5000 mN or less as measured by a micro-compression tester, containing no inorganic binders or organic components, with 90% or more of the total particles having a particle size of 0.2 mm or more and 1.7 mm or less, and a bulk density of 0.9 g / cm 3 The above is the layered manganese oxide molded body.
2. Having a crushing strength of 2000 mN or more and 4000 mN or less as measured by a micro-compression testing machine, Composition formula A having a bulk density of 1.0 g / cm 3 or more x MnO 2 2. The layered manganese oxide molded product according to claim 1, wherein A represents one or more alkali metals selected from sodium and potassium, and 0.2≦x≦0.
6.
3. 3. The layered manganese oxide molded product according to claim 1, wherein the interlayer distance of the layered manganese oxide is from 7.0 angstroms to 7.3 angstroms.
4. The layered manganese oxide molded body according to any one of claims 1 to 3, wherein the FWHM of the 001 peak when assigned to a hexagonal crystal in a powder X-ray diffraction experiment is 0.4° or more and 3.5° or less.
5. Composition formula A x MnO 2 A is an alkali metal containing at least sodium and potassium, and 0.4≦x≦0.6; The layered manganese oxide molded body according to any one of claims 1 to 4, wherein the FWHM of the 001 peak when assigned to a hexagonal crystal in a powder X-ray diffraction experiment is 2.5° or more and 3.5° or less.
6. The layered manganese oxide molded body according to any one of claims 1 to 4, wherein the alkali metal is potassium.
7. The layered manganese oxide molded body according to any one of claims 1 to 6, which has a stirring wear rate of 15% by weight or less.
8. The layered manganese oxide molding according to claim 1, which is a birnessite-type layered manganese oxide.
9. The layered manganese oxide molded body according to any one of claims 1 to 8, having a carbon concentration of 3000 ppm or less.
10. A metal salt aqueous solution containing at least manganese and having an alkaline earth metal concentration of less than 1500 ppm, an alkali metal aqueous solution, and an oxidizing agent are mixed in a reaction vessel having an alkali metal / manganese molar ratio of 2 to 10, an oxidation-reduction potential of the reaction solution relative to a saturated calomel electrode of -0.2 V to 0.6 V, a temperature of 0°C to 100°C, and a stirring power requirement per unit volume of 0.5 kW / m 3 The method for producing a layered manganese oxide molded body according to any one of claims 1 to 9, comprising: obtaining a mixed aqueous solution by mixing the above ingredients, precipitating a slurry in the mixed aqueous solution at a solids concentration of 1 wt % or more and 5 wt % or less, filtering the slurry, and then thermally curing the precipitated substance at a temperature of 40° C. or more and 200° C. or less.
11. The method for producing a layered manganese oxide molded body according to claim 10, wherein the alkali metal is potassium.
12. 12. The method for producing a layered manganese oxide molded body according to claim 10 or 11, wherein the oxidizing agent is at least one selected from the group consisting of hydrogen peroxide, oxygen, air, and peroxodisulfates.
13. 13. The method for producing a layered manganese oxide molded body according to any one of claims 10 to 12, wherein the precipitated substance precipitated in the mixed aqueous solution is buserite having an interlayer distance of 9 angstroms or more and 10 angstroms or less, and the precipitated substance becomes birnessite having an interlayer distance of 7.0 angstroms or more and 7.3 angstroms or less during a thermal curing process.
14. A strontium adsorbent comprising the layered manganese oxide molded article according to any one of claims 1 to 9.
Citation Information
Patent Citations
Positive active material for lithium secondary battery and its manufacture
JP1999317225A
Sulfur oxide adsorbent and emission control
JP2007527783A
Heavy metal treating agent and method of making heavy metal-contaminated matter harmless
JP2009254920A
Method for producing manganese oxide
JP2011207725A
Metal-substituted trimanganese tetraoxide and method for producing the same, and method for producing lithium manganese complex oxide using the same
JP2013230966A